Retrotransposon-Based Genetic Diversity of Rhodiola rosea L. (Crassulaceae) from Kazakhstan Altai - Oxana Khapilina; Ainur Turzhanova; Moldir Zhumagul; Damelya Tagimanova; Olesya Raiser; Serik Kubentayev; Vladislav Shevtsov; Maria Hohn (Diversity)
The analysis of genetic diversity in natural populations of valuable medicinal plant species experiencing overexploitation is a key aspect of their natural conservation strategy. Mobile genetic elements and other interspersed repeats, which are major components of eukaryotic genomes, serve as effective tools for studying plant biodiversity and variability. The genetic diversity of four valuable medicinal plant Rhodiola rosea L. populations was investigated using the inter-repeat amplified PCR method with inter-priming binding sites (iPBSs) for genome profiling. At the interpopulation level, unique amplicons characteristic of specific R. rosea populations were identified. Molecular variance analysis revealed that the biodiversity of R. rosea populations in the Kazakh Altai region is 56% attributed to interpopulation differences and 44% to intrapopulation differences. It was shown that populations located in favorable environmental conditions have greater genetic diversity compared to those in extreme habitats. This study identified a high degree of polymorphism among R. rosea populations using the inter-repeat amplified PCR method. The genetic diversity of the populations ranged from 0.105 to 0.156, with an average heterozygosity of 0.134. The findings provide new insights into the population structure of R. rosea in the Kazakh Altai, enabling the identification of different genotypes, which will significantly complement traditional methods for conserving this valuable medicinal plant.